Multiple actuation microvalves in wax microfluidics. Issue 20 (12th September 2016) - Díaz-González, María; Fernández-Sánchez, César; Baldi, Antonio
Abstract : A new type of electrically controlled and fully integrated wax microvalve is described. The valve is designed for multiple actuation and has a small footprint, fast response and low energy consumption. Abstract : Microvalves are an essential component of microfluidic devices. In this work, a low-consumption (<35 mJ), fast-response (<0.3 s), small footprint (<0.5 mm 2 ) wax microvalve capable of multiple actuation is described. This phase-change microvalve is electrically controlled, simple to operate and can be easily fabricated as a fully integrated element of wax microfluidic devices through a special decal-transfer microlithographic process. The valve is inherently latched and leak-proof to at least 100 kPa. A minimum pressure of 3 kPa is required for valve opening. Maximum pressures for a successful closing in air and liquid are 90 and 40 kPa, respectively. The wax valve exhibits reversible open–close behaviour without failure for up to 10 actuation cycles in air (60 kPa) and 5 in water (30 kPa). To the best of our knowledge, this microvalve has the lowest energy consumption (two orders of magnitude lower) reported so far for a plug-type phase-change valve. Furthermore, its size, actuation mechanism and fabrication technology make it suitable for large-scale integration in microfluidic devices. Detailed characteristics in fabrication and actuation of the wax microfluidic valve as well as a test example of its performance for liquid dispensing are reported.